2015
DOI: 10.1177/1049731515594425
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Kessler Psychological Distress Scale (K6) Among Emerging Adults

Abstract: Objective: Confirmatory factor analysis was used to assess the factor structure of the 6-item version of the Kessler Psychological Distress Scale (K6). Methods: A subsample of emerging adults, aged 18-29 (n ¼ 20,699), from the 2013 National Survey of Drug Use and Health were used in this study. Results: Each of the models (one-factor, two-factor depression and anxiety and second-order two-factor psychological distress by depression and anxiety) demonstrated good fit, with significant loadings on each factor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 40 publications
5
48
0
5
Order By: Relevance
“…Nevertheless, this model had a poor t with the data from a large sample of adolescents in Australia, and a modi ed single-factor model was proposed instead [21], allowing residual correlations among several items. Moreover, two-factor models were also reported in several studies [6,7,22,23]. Kessler et al found a two-factor solution emerged in the Indian sample, with an item ("Everything was an effort") loading on the second factor [6].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, this model had a poor t with the data from a large sample of adolescents in Australia, and a modi ed single-factor model was proposed instead [21], allowing residual correlations among several items. Moreover, two-factor models were also reported in several studies [6,7,22,23]. Kessler et al found a two-factor solution emerged in the Indian sample, with an item ("Everything was an effort") loading on the second factor [6].…”
mentioning
confidence: 84%
“…A two-factor model ("Depressed", "Nervous", and "Restless or dgety" on the rst factor, while "Hopeless", "Everything was an effort ", and "Worthless "on the second factor) had a better and an acceptable t to the data, χ2=18.912, df=4, CFI=1.00, TLI=0.999, and RMSEA=0.024 (90% CI 0.014, 0.035). In CFA, We tested the one-factor model and the two-factor model derived from EFA, as well as three other two-factor models proposed by Kessler et al [6], Lee et al [22] and Bessaha [7]. In Kessler et al's model, an item ("Everything was an effort") loads on the second factor, while all other ve items load on the rst factor.…”
Section: Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Se preguntó a los encuestados qué tan a menudo (en los últimos 30 días) se sintieron nerviosos, sin esperanza, intranquilos, deprimidos, que todo costaba mucho esfuerzo o que no valían nada. Esta escala tiene un rango de 0 a 24 puntos (a mayor puntaje, mayor malestar emocional) y corresponde a una adaptación en español, del instrumento de 10 ítems (k10), 31,32 validada en la población mexicana. 33 Los factores sociales considerados fueron estado civil (con/sin pareja), ocupación (con/sin empleo), escolaridad (primaria o menor, secundaria, bachillerato y universidad o más) e índice de bienestar, el cual se construyó a través de un análisis de componentes principales sobre los bienes en el hogar del encuestado y está expresado en quintiles, siendo el primer quintil el índice de bienestar más bajo.…”
Section: Factores Asociados Con La Dependencia Al Tabacounclassified
“…Confirmatory factor analysis (CFA), as used elsewhere (Easton et al, 2017;Bessaha, 2017;Lee et al, 2012), was used to examine how well the Bangla K6 items represent one or more latent constructs. CFA offers the testing of hypothesis that a relationship between observed variables and their underlying latent constructs exists.…”
Section: Data Analysesmentioning
confidence: 99%